ON IDENTIFICATION OF CONCRETE PLASTICIZING ADDITIVES - P. I. Yukhnevskiy; G. T. Schirokij (Наука и техника)
Quality problem of chemical additives comes down in general to their objective and independent evaluation. As an identification is not made during product delivery for testing and while carrying out the testing there is difference in the results of investigations and finally construction products suffer from their poor quality. In this connection, it is proposed to make some alterations to revised version of the STB 1112 and GOST 30459, so that while supplying chemical additives for certification testing a certificate on additive quality should contain a standard of IR-spectra with active components. Simultaneously, the standard should be applied for additive testing results in accordance with rate efficiency criteria  for GOST 30459. Such norms are accepted for similar European standards.The paper presents a standard method for identification of organic additives according to IR-spectra, characteristic absorption bands for the Lignopan-type  additives and naphthalene formaldehyde super-plasticizer C-3. However, due to the fact that it is not possible to judge number of functional groups in the product by  absorption band size but it is possible only to assess their availability so it is recommended to use other methods. As an additional characteristics it is proposed to determine magnitude of the dipole moment in a  plasticizer-additive molecule. The authors previously developed a technique and  determined dipole moments in super-plasticizer-additives as in the form of powder so in the form of aqueous solutions, correlation relationship of water reduction additive capability with the magnitude of dipole moment. It has been proposed to manufacturers of plasticizing additives for concrete along with IR-spectra in the technical documentation to indicate a magnitude of the molecule dipole moment  as a generalized characteristics that determines its plasticizing properties.